A Comparative Study on the Effects of Co-Digesting Molasses with Palm Oil Mill Effluent (POME) or Chicken Manure on Biomethane Yield - Aziz Izzah Farhana Ab; Man Hasfalina Che; Shukery Mohamad Firdza Mohamad; Jaffar Mudzaffar Afzan Mohd; Shern Hew Yoong; Omar Rozita; Jamali Nur Syakina (E3S Web of Conferences)
This study evaluates the performance of molasses (MS) co-digested with palm oil mill effluent (POME) and chicken manure (CM) to enhance methane production. The co-digestion of MS and CM at an optimum ratio of 7:1 yielded the highest biogas (520.2 mL/g VS) and methane (450.0 mL CH4/g VS), with a methane content of 86.5%, significantly outperforming the co-digestion of MS and POME, which achieved a maximum methane yield of 208.4 mL CH4/g VS and a methane content of 61.1%. Kinetic modelling using the modified Gompertz equation demonstrated a strong correlation between predicted and observed results, with R2 values ranging from 0.986 to 0.996, confirming the model’s reliability for predicting biogas yields. The MS and CM combination also exhibited faster biogas production initiation, shorter lag phases, and more excellent process stability, attributed to the balanced carbon-to-nitrogen ratio and CM’s buffering capacity. These findings highlight the superior performance of the MS and CM combination in anaerobic co-digestion, offering a more efficient approach to biogas production compared to MS and POME. This research contributes to optimising co-digestion systems and provides a foundation for the scaling up of bioreactor designs, enhancing renewable energy production from organic waste.